Monetary model of exchange rate for Thailand : long-run relationship and monetary restrictions. - Liew, Venus Khim Sen; Baharumshah, Ahmad Zubaidi; Puah, Chin Hong (Routledge, 2009)
This paper examines the long-run relationship between exchange rate and its determinants based on the flexible-price monetary model. The multivariate cointegration approach is adopted to attain our objective of this study. The empirical results provide evidence favoring the monetary approach to exchange rate for a small and open emerging economy, namely Thailand. In addition, the validity of the underlying assumptions of the monetary approach to the determination of exchange rate is established. The findings suggest that exchange rate players may effectively monitor and forecast the exchange rate movement via the money supplies, incomes, and interest rates variables of both Thailand and Japan. Besides, one has to follow the economic development of Thailand's major trading partner, Japan, to understanding the movement of exchange rate for Thailand. Moreover, our findings add new insights to accompany previous studies that documented the important influence of the US in the emerging Asian economies.